2004
DOI: 10.1093/bja/aeh265
|View full text |Cite
|
Sign up to set email alerts
|

Fast-tracking (bypassing the PACU) does not reduce nursing workload after ambulatory surgery †

Abstract: Bypassing the PACU after these short outpatient procedures significantly decreases recovery time without compromising patient satisfaction. However, the overall nursing workload and the associated cost were not significantly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 16 publications
0
38
0
6
Order By: Relevance
“…This result is similar to published work from the adult literature. 8,9 The physiological scoring system used allows for assessment of a range of physiological parameters, including level of consciousness, respiration, hemodynamics, and postoperative outcomes, including bleeding from the surgical site. More than three-fourths of patients had a CBD time that was less than the corresponding TBD time, demonstrating the potential for the physiological scoring system to save time spent in the PACU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is similar to published work from the adult literature. 8,9 The physiological scoring system used allows for assessment of a range of physiological parameters, including level of consciousness, respiration, hemodynamics, and postoperative outcomes, including bleeding from the surgical site. More than three-fourths of patients had a CBD time that was less than the corresponding TBD time, demonstrating the potential for the physiological scoring system to save time spent in the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological score (maximum score, 14; Table 1) was a combination of the systems of Aldrete 8 and Chung 11 evaluating respiration, circulation, level of consciousness, and postoperative outcomes. Scores were recorded every 15 min starting upon arrival in the PACU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Both Song and Williams et al have observed the phenomenon of an increased number of interventions in phase 2 recovery. 8,28 They have recognized that shortening phase 1 recovery time simply transfers the workload to phase 2 recovery; however, the extra interventions in the low-dose spinal group were not related to pain management or bladder management.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the fast-track group, 81% of patients bypassed the PACU successfully. Ninetyseven percent of patients undergoing arthroscopy met fast-track criteria and were able to bypass the PACU.…”
Section: Discharge Criteria Scorementioning
confidence: 99%